Reduced excitatory neurotransmitter levels in anterior insulae are associated with abdominal pain in irritable bowel syndrome. Issue 9 (September 2019) - Bednarska, Olga; Icenhour, Adriane; Tapper, Sofie; Witt, Suzanne T.; Tisell, Anders; Lundberg, Peter; Elsenbruch, Sigrid; Engström, Maria; Walter, Susanna
Abstract : Abstract: Irritable bowel syndrome (IBS) is a visceral pain condition with psychological comorbidity. Brain imaging studies in IBS demonstrate altered function in anterior insula (aINS), a key hub for integration of interoceptive, affective, and cognitive processes. However, alterations in aINS excitatory and inhibitory neurotransmission as putative biochemical underpinnings of these functional changes remain elusive. Using quantitative magnetic resonance spectroscopy, we compared women with IBS and healthy women (healthy controls [HC]) with respect to aINS glutamate + glutamine (Glx) and γ-aminobutyric acid (GABA+) concentrations and addressed possible associations with symptoms. Thirty-nine women with IBS and 21 HC underwent quantitative magnetic resonance spectroscopy of bilateral aINS to assess Glx and GABA+ concentrations. Questionnaire data from all participants and prospective symptom-diary data from patients were obtained for regression analyses of neurotransmitter concentrations with IBS-related and psychological parameters. Concentrations of Glx were lower in IBS compared with HC (left aINS P < 0.05, right aINS P < 0.001), whereas no group differences were detected for GABA+ concentrations. Lower right-lateralized Glx concentrations in patients were substantially predicted by longer pain duration, while less frequent use of adaptive pain‐coping predicted lower Glx in left aINS. Our findings provide first evidence for reduced excitatory but unaltered inhibitory neurotransmitter levels in aINS in IBS. The results also indicate a functional lateralization of aINS with a stronger involvement of the right hemisphere in perception of abdominal pain and of the left aINS in cognitive pain regulation. Our findings suggest that glutaminergic deficiency may play a role in pain processing in IBS. Abstract : Supplemental Digital Content is Available in the Text.Quantitative magnetic resonance spectroscopy of anterior insula reveals decreased glutamatergic neurotransmitter concentrations in patients with irritable bowel syndrome and hemisphere-specific associations with pain severity and pain-related coping.